Triple‐Negative Breast Cancer in Ghanaian Women: The Korle Bu Teaching Hospital Experience. Issue 6 (November 2015) - Der, Edmund M.; Gyasi, Richard K.; Tettey, Yao; Edusei, Lawrence; Bayor, Marcel T.; Jiagge, Evelyn; Gyakobo, Mawuli; Merajver, Sofia D.; Newman, Lisa A.
Abstract: Breast cancers that have negative or extremely low expression of estrogen receptor and progesterone receptor and non‐amplification of human epidermal growth factor receptor‐2 (HER2)/ neu are termed triple‐negative breast cancer (TNBC). The majority of TNBC tumors belong to the biologically aggressive basal subtype, and they cannot be managed with targeted endocrine or anti‐HER2/ neu agents. In western, high resource environments, risk factors for TNBC include younger age at diagnosis and hereditary susceptibility. Women of African ancestry in the United States and in continental Africa have higher frequencies of TNBC, prompting speculation that this risk may have an inherited basis and may at least partially explain breast cancer survival disparities related to racial/ethnic identity. Efforts to document and confirm the breast cancer burden of continental Africa have been hampered by the limited availability of registry and immunohistochemistry resources. Our goal was to evaluate the breast cancers diagnosed in one of the largest health care facilities in western Africa, and to compare the frequencies as well as risk factors for TNBC versus non‐TNBC in this large referral tertiary hospital. The Korle Bu Teaching Hospital is affiliated with the University of Ghana and is located in Accra, the capital of Ghana. We conducted an institutional, Department of Pathology‐based review of the breast cancer cases seen at this facility for the 2010 calendar year, and for which histopathologic specimens were available. The overall study population of 223 breast cancer cases had a median age of 52.4 years, and most had palpable tumors larger than 5 cm in diameter. More than half were TNBC (130; 58.3%). We observed similar age‐specific frequencies, distribution of stage at diagnosis and tumor grade among cases of TNBC compared to cases of non‐TNBC. Ghanaian breast cancer patients tend to have an advanced stage distribution and relatively younger age at diagnosis compared to Caucasian Americans and African Americans. The triple‐negative molecular marker pattern was the most common subtype of breast cancer seen among this sample of Ghanaian women, regardless of age, tumor grade, or stage of diagnosis. Research into the molecular pathogenesis of TNBC may help elucidate the reasons for its increased prevalence among women with African ancestry.